The first reported case of drug‐induced hemolytic anemia caused by dimethyl fumarate in a patient with multiple sclerosis. Issue 5 (31st January 2019) - Quintanilla‐Bordás, Carlos; Castro‐Izaguirre, Emma; Carcelén‐Gadea, María; Marín, María
Abstract : BACKGROUND: Drug‐induced hemolytic anemia is a rare and potentially fatal complication of drug treatment. Specific laboratory tests are crucial to confirm the diagnosis. CASE REPORT: A 38‐year‐old woman on treatment with dimethyl fumarate for multiple sclerosis presented with a 7‐day history of weakness and fatigue. Laboratory tests revealed profound hemolytic anemia with hemoglobin levels of 4.7 g/dL (reference, 12.5–16.0), decreased haptoglobin, increased reticulocyte count, and increased indirect bilirubin. A first direct antiglobulin test was negative. The patient was started on prednisone 1 mg/kg/day, and dimethyl fumarate was withdrawn. A blood sample was drawn on Day 7 and sent to a reference laboratory. A direct antiglobulin test performed 7 days later was positive. Furthermore, an indirect antiglobulin test was positive only in the presence of the drug. RESULTS: The patient did not receive a blood transfusion, recovered clinically during the following days, and was discharged on Day 7. On Day 36, the patient's RBCs had normalized. She was changed to another disease‐modifying treatment for her multiple sclerosis, and at 10‐month follow‐up she remained stable without any notable adverse effects. CONCLUSION: This case describes the first report of a dimethyl fumarate–induced hemolytic anemia. Laboratory results should always be interpreted within the clinical context. Specific laboratory expertise is often needed, given the complexity of the field.